Recreational Roblox Usage and English Language Learning Engagement Among University Students - Larekeng, Siti Hajar; Sahabuddin, Ilham; Wahyuddin, Wahyuddin (LETS: Journal of Linguistics and English Teaching Studies, 2026)
This study investigates the relationship between recreational Roblox usage and English language learning engagement among university students, addressing a gap in literature focused largely on younger learners or structured pedagogical settings.  Within the framework of technology-enhanced language learning (TELL), the research examines how this immersive gaming platform shapes the language learning concentration and academic motivation of EFL university students. Employing a Sequential Explanatory Mixed-Methods Design, the study collected data from 53 university students  via questionnaires and semi-structured interviews. This data were then analyzed using descriptive statistics and Spearman rank correlation. The results indicate that Roblox usage is predominantly social and recreational rather than compulsive.  Although 58.5% of respondents spend  more than two hours per session,  the majority maintain functional boundaries by prioritizing English assignments  over gaming. Crucially, no participants reported severe psychological dependency, though a segment  admitted to occasional procrastination. Furthermore, the platform's English-dominant interface and collaborative gameplay  expose students to authentic language input, fostering informal second language acquisition (SLA) through peer interaction. Ultimately, the study concludes that while severe concentration disruption is uncommon, subtle procrastination remains a  self-regulation challenge. These findings   highlight the need for targeted digital wellness frameworks and pedagogical guidance,  which can help EFL students harness immersive recreational gaming as a language learning tool   while preserving academic focus.